2016
DOI: 10.1016/j.devcel.2016.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Actin Rings of Power

Abstract: Circular or ring-like actin structures play important roles in various developmental and physiological processes. Commonly, these rings are composed of actin filaments and myosin motors (actomyosin) that, upon activation, trigger ring constriction. Actomyosin ring constriction, in turn, has been implicated in key cellular processes ranging from cytokinesis to wound closure. Non-constricting actin ring-like structures also form at cell-cell contacts, where they exert a stabilizing function. Here, we review rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 186 publications
(212 reference statements)
4
73
1
2
Order By: Relevance
“…This thereby allows both actin structures to co-exist in condition of low RhoA activity. Actomyosin rings are critical cytoskeletal structures contributing to essential processes, such as cytokinesis and wound healing, in epithelia944454647. Actomyosin ring is also critical to adjust the size of tunnels between endothelial cells when neutrophils undergo endothelial diapedesis8.…”
Section: Discussionmentioning
confidence: 99%
“…This thereby allows both actin structures to co-exist in condition of low RhoA activity. Actomyosin rings are critical cytoskeletal structures contributing to essential processes, such as cytokinesis and wound healing, in epithelia944454647. Actomyosin ring is also critical to adjust the size of tunnels between endothelial cells when neutrophils undergo endothelial diapedesis8.…”
Section: Discussionmentioning
confidence: 99%
“…Apical constriction is driven by cortical tension-generating actomyosin contractions that are transmitted to neighboring cells via apically localized cadherins (reviewed in [Heisenberg and Bellaïche, 2013; Martin et al, 2009; Pilot and Lecuit, 2005; Schwayer et al, 2016]). We demonstrate that Fgf-dependent Notch signaling cell-autonomously, and downstream of Fgf signaling upregulates adherens and tight junction molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that p120-catenin levels altered the tension of the plasma membrane. Altogether, this shows that p120-catenin is a central hub which co-ordinates cell adhesion, endocytosis, and actin dynamics with tissue tension.requires Rho-kinase for recruitment to AJs [76][77][78].…”
mentioning
confidence: 85%